Swapping of Periplasmic Domains between Brucella suis VirB8 and a pSB102 VirB8 Homologue Allows Heterologous Complementation - Patey, Gilles (American Society for Microbiology, 2006)
A Brucella suis mutant with a nonpolar deletion in the virB8 gene was attenuated in a macrophage infection model. Complementation with the B. suis VirB8 protein expressed from the virB promoter restored virulence. Expression of TraJ, a VirB8 homologue from plasmid pSB102, did not restore virulence; however, virulence was partially restored by a chimeric protein containing the N terminus of the B. suis VirB8 protein and the C-terminal periplasmic domain of TraJ.